A simple self‐reported adherence tool as a predictor of viral rebound in people with viral suppression on antiretroviral therapy. Issue 2 (17th July 2015) - O'Connor, JL; Gardner, EM; Esser, S; Mannheimer, SB; Lifson, AR; Telzak, EE; Phillips, AN; ,
Abstract : Objectives: The aim of the study was to investigate the relationship between self‐reported antiretroviral therapy (ART) adherence and virological outcomes in the multinational Strategies for Management of Antiretroviral Therapy (SMART) study. Methods: Eligible participants were from the continuous ART arm and had at least one viral load (VL) ≤ 50 HIV‐1 RNA copies/mL and a subsequent VL value (VL pair). Self‐reported adherence was measured at each visit using a five‐point Likert scale which employed a 7‐day recall. High adherence was defined as taking 'all pills every day' (level 1) for every regimen component; all others had suboptimal adherence (levels 2 − 5). In individuals with VL suppression (≤ 50 copies/mL), the association between adherence (at the time of VL suppression) and VL rebound (> 200 copies/mL at next visit) was assessed using multivariable logistic regression with generalized estimating equations. Results: A total of 10 761 sets of VL pairs from 1986 participants were included in the study. For 1220 (11%) VL pairs, adherence was suboptimal. For 507 VL pairs (5%), VL rebound occurred. The risk of rebound generally increased as adherence decreased: 4.2% for level 1, 7.7% for level 2, 16.3% for level 3, 9.4% for level 4 and 12.9% for level 5. In multivariable analysis, suboptimal adherence at the time of suppression was associated with a 50% increased odds of experiencing subsequent VL rebound [odds ratio (OR) 1.51; 95% confidence interval (CI) 1.19–1.92; P  = 0.0023], compared with high adherence. Conclusions: Self‐reported suboptimal adherence in people with VL suppression is associated with an increased risk of VL rebound. Our findings highlight the importance of continued adherence counselling, even in people with VL suppression, and to ensure that people with HIV infection maintain excellent adherence in order to minimize the risk of VL rebound.